Association of normal levels of both haemoglobin and white blood cells count with normality of complete blood count - Maysem Mouayad Alwash; Shaymaa Wahbi Salman; Taymaa Moayad Ahmed (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the use of haemoglobin and white blood cell count together in predicting the normality of other complete blood count parameters and blood film. Method: The prospective study was conducted from August to November 2021 at Al-Yarmouk Teaching Hospital, Baghdad, Iraq, and comprised adult individuals of either gender who were advised blood test by physicians in the outpatient department. Patients with normal haemoglobin and white blood cell counts were placed in group A, while those with abnormal counts of the two parameters were placed in group B. Examination of blood smears morphology was done in both groups. Data was analysed using SPSS 26. Results: Of the 200 subjects, 100(50%) were in group A; 58(58%) males and 42(42%) females with mean age 51.09±18.8 years. There were 100(50%) subjects in group B; 52(52%) males and 48(48%) females with mean age 47.58±15.5 years (p>0.05). In group A, 70(70%) cases showed normal complete blood count parameters and abnormal morphology of 1+ grading in 13(13%). The results were significantly different than group B (p<0.05). Conclusion: Normal haemoglobin and white blood cell count was found to a good marker for the normality of other complete blood count parameters. Key Words: Leukocyte, Haemoglobins, Haematological